The Comparative Strengths of Orthopaedic Staples Versus a 2.7 mm T Plate in the Stabilisation of Distal Radial Osteotomies - Thomson, M. J.; Read, R. A.; Day, R. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Distal radial osteotomies were performed in 20 limbs from ten cadaver specimens. Ten bones were stabilised with two × 1.6 mm surgical bone staples and ten were stabilised with a 2.7 mm T platea. The radii were removed and the osteotomies were biomechanically tested in torsion initially, and then to failure in bending. Statistically significant differences were not found between the two types of repair in torsional stiffness, bending stiffness, deflection to failure in bending, or load to failure in bending. Orthopaedic staples are a simple, cost-effective alternative to bone plates for stabilisation of distal radial osteotomies.Bilateral distal radial osteotomies were created in dog cadavers and then repaired with either two bone staples or a 2.7 mm T plate. The limbs were then tested in vitro to compare the relative strengths of the repairs in torsion and bending. Statistically significant differences were not found between the two methods of stabilisation.
Keywords: Distal radial osteotomies; orthopaedic staples